Impact of the COVID-19 pandemic on perceived access and quality of care in German people with parkinsonism - Marlena van Munster; Marlena van Munster; Marcel R. Printz; Eric Crighton; Tiago A. Mestre; David J. Pedrosa; David J. Pedrosa; iCARE-PD Consortium (Frontiers Media S.A., 2023)
Due to the heterogeneous clinical presentation, people with Parkinsonism (PwP) develop individual healthcare needs as their disease progresses. However, because of limited health resources during the COVID-19 pandemic, many patients were put at risk of inadequate care. All this occurred in the context of inequitable healthcare provision within societies, especially for such vulnerable populations. This study aimed to investigate factors influencing satisfaction and unmet need for healthcare among PwP during the COVID-19 pandemic in Germany. Analyses relied on an anonymous online survey with a 49-item questionnaire. We aimed at describing access to health services before and during the early stages of the pandemic. To this end, a generalized linear model was used to derive significant predictors and a stepwise regression to subsummarize the main factors of perceived inadequate care. In total, 551 questionnaires showed that satisfaction with Parkinsonism-related care decreased significantly during the pandemic (p < 0.001). In particular, factors such as lower educational level, lower perceived expertise of healthcare providers, less confidence in remote care, difficulties in obtaining healthcare, and restricted access to care before the pandemic but also lower densities of neurologists at residence and less ability to overcome barriers were indicative of higher odds to perceive unmet needs (p < 0.05). The results unveil obstacles contributing to reduced access to healthcare during the COVID-19 pandemic for PwP. These findings enable considerations for improved provision of healthcare services to PwP.